Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Which of these terms is greater ?

$2x-6y+1$ or $1$

if $x^4 + 3y^2=0$

According to the text they are equal ?How is that ?

share|cite|improve this question
It boils down to comparing $2x-6y$ and $0$, which further reduces to comparing $x$ and $3y$. – Host-website-on-iPage Jul 13 '12 at 5:36
up vote 12 down vote accepted

But since $x^2$ and $3y^2$ are positive, (assuming $x,y$ real) we have that $x^2+3y^2=0$ forces $x=y=0$ so the text is correct!

share|cite|improve this answer

What number system are $x,y$ in? If $x,y\in\mathbb{R}$, then it is simple, since $x^4$, $3y^2$ $\ge 0$, we must have that $x,y=0$, hence $2x-6y+1=1$.

share|cite|improve this answer

If sum of squares is $0$ then each term of the series is $0$ individually (if they belong to $\Bbb R$) $\implies$ $x=0,y=0$ in your problem which gives $2x-6y+1=1$.

share|cite|improve this answer

we know that for positive terms Arithmetic Mean $\geq$ Geometric Mean

i.e. $$(x^4 + y^2 + y ^2 + y^2)/4 \geq \sqrt[4]{(x^4)(y^2)(y^2)(y^2)}$$

i.e. $(x^4 + 3y^2)/4 \ge (x)(y)\sqrt{y}$

i.e. $(x)(y)\sqrt{y} \le (x^4 + 3y^2)/4$

i.e. $(x)(y)\sqrt{y} \le 0$

for $\sqrt{y}$ to be real $y \ge 0$

i.e. $y \ge 0$ ------- (1)

i.e. $x \le 0$ ------- (2)

we know that for positive terms Arithmetic Mean $\geq$ Harmonic Mean

i.e. $$(x^4 + y^2 + y^2 + y^2)/4 \geq {4/(1/x^4 + 1/y^2 + 1/y^2 + 1/y^2)}$$

i.e. $$(x^4 + 3y^2)(1/x^4 + 3/y^2) \geq {(4)(4)}$$

i.e. $$(1 + 3(y/x^2)^2 + 3(x^2/y)^2 + 9) \geq {16}$$

i.e. $$3(y^2/x^4) + 3(x^4/y^2) \geq {6}$$

i.e. $$(y^2/x^4) + (x^4/y^2) \geq {2}$$

i.e. $$(y^4 + x^8) \geq {2(y^2)(x^4)}$$

i.e. $$(y^2 - x^4)^2 \geq {0}$$

i.e. $$(x^4 - y^2)^2 \geq {0}$$

consider $$x^4 \geq {y^2}$$

i.e. $$(x^4 - y^2) \geq {0}$$

i.e. $$(x^2 - y)(x^2 + y) \geq {0}$$

i.e. $$(x^2 - y)(x^2 + y) \geq {0}$$

i.e. $$(y - x^2)(y + x^2) \leq {0}$$

i.e. ${-x^2} \leq y \leq {x^2}$ ------- (3)

The three inequalities listed above will hold concurrently only when $x = y = 0$

share|cite|improve this answer
Please use $LATEX$ – Aang Jul 13 '12 at 6:57
x^4 + 3y^2 = 0 implies each term x^4 and y^2 are individually equal to 0 – Rajesh K Singh Jul 13 '12 at 6:58
NOTE : for sqrt(y) to be real y ge 0 – Rajesh K Singh Jul 13 '12 at 14:25

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.